Pemberdayaan Masyarakat Desa Sidorejo dalam Menghadapi Pandemi Covid-19 di Era New Normal - Dimas Fanny Hebrasianto Permadi`; Anggita Mawar Sari; Belqis Nur Ivada Navalufi; Dika Dwi Kurniawan; Elisa Dwi Okta Sari; Endang Sri Rahayu; Fahrur Riska Ulinnuha; Imam Wahyudi; Ivanda Vipriyandhito; Khoirul Mujib; Melinda Sukma Ayu Adien Arera; Moh Aris Triprastya; Priadi Priadi; Riyonaldi Dwia Juang Saputra; Rofiatul Muzayyanah; Sri Lestari; Wahyu Setiawan; Yogi Prasetyo; Yordan Setyawan (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2021)
Human life around the world is changing, including Indonesia, especially the people of Sidorejo Village. This change is due to the Covid-19 virus which forces people to adopt a new daily life. In this case, globally, people's social life must be able to adapt to new conditions. Human life everywhere enters a space called the New Normal. This article wants to explain how to implement the new adaptation of the Sidorejo Village community. A social condition of the community or individual behavior to prevent the transmission of the Covid-19 virus.